Invasive squamous cell carcinoma arising from an intraductal oncocytic papillary neoplasm demonstrating shared ATP1B1::PRKACA gene fusion - Wai Szeto; Safa Alshaikh; Javier A. Arias-Stella, III; Yuman Fong; Rifat Mannan (Elsevier, 2024)
Intraductal oncocytic papillary neoplasms (IOPN) are rare cystic pancreatic neoplasms marked by oncocytic cells and intricate papillary structures. While typically slow-growing, approximately one-third of IOPN cases are associated with invasive adenocarcinoma. In this report, we present an extremely rare case of invasive squamous cell carcinoma arising in the background of IOPN. A 74-year-old man underwent a central pancreatectomy due to an incidentally discovered cystic mass in the pancreatic body. Histological examination revealed IOPN with regions of invasive squamous cell carcinoma. Next-generation sequencing identified the characteristic ATP1B1::PRKACA fusion in both the IOPN and squamous cell carcinoma components. To the best of our knowledge, this is the first documented instance of invasive squamous cell carcinoma originating from an IOPN.